C-Reactive Protein (CRP) and Health Resort Reaction. (28th January 2020) - Kuciel-Lewandowska, Jadwiga; Kasperczak, Michal; Szybinska, Malgorzata; Gnus, Jan; Paprocka-Borowicz, Malgorzata
Abstract : Incident tissue-damaging factors trigger a systemic response manifested by inflammatory reaction. Acute-phase proteins are a diagnostic and prognostic marker in various systemic homeostasis disorders. In the course of health resort therapy, a so-called health resort reaction is observed presenting with, e.g., exacerbation of organ-related disorders, elevated body temperature, increased erythrocyte sedimentation rate, and leukocyte counts. The objective of the study was to demonstrate a change in the concentration of C-reactive protein (CRP) as a result of health resort radon therapy as well as to determine the relationship between this change and the phenomenon known as health resort reaction. The study was conducted in Swieradow-Zdroj resort. The study population consisted of patients undergoing radon-active water bath treatment. Standard tests were used to determine CRP levels before the treatment as well as 5 and 18 days into the treatment. The study group consisted of n  = 34 patients with osteoarthritis and spondyloarthritis. The control group consisted of 17 employees of the health resort who were also burdened with osteoarthritis or spondyloarthritis yet did not undergo radon therapy and had absolutely no contact with radon materials. The study revealed no statistically significant increase in the concentration of CRP. This trial is registered with NCT03274128 . The study was carried out as part of the statutory task SUB.E060.19.001.